Relative map location of the rep and rho genes of Escherichia coli. - Tessman, I (1982)
The rep gene of Escherichia coli was mapped between ilvC and rho by three-factor P1 transductional crosses and also by complementation with a set of lambda transducing phages that contain known amounts of bacterial DNA linked to ilvC. The physical distance between ilvC and rep and between rep and rho were calculated with an accuracy of +/- 0.4 kilobase to be 0 less than or equal to ilvC-rep less than or equal to 3.4 kilobases and 2.0 less than or equal to rep-rho less than or equal to 6.0 kilobases. It was shown that rho-15 is Gro+ for phage ST-1. An ilv::Tn10 mutation was located in ilvY.